MAPPING OF THE PEAK GROUND ACCELERATION AND EARTHQUAKE INTENSITY IN PADANG CITY USING EMPIRICAL FORMULATION WITH ACCELEROGRAPH DATA VALIDATION - Adya Mustika Sari; - Syafriani; Fajri Syukur Rahmatullah (PILLAR OF PHYSICS, 2021)
The city of Padang is an area severely affected by the earthquake that occurred in the Subduction zone. Earthquakes with large magnitudes greatly affect the damage to buildings, one of the factors that can determine the size of the damage is the peak ground acceleration. The peak ground acceleration and earthquake intensity in Padang City can be calculated using an empirical formula. The research area is on the grid with a distance of 0,02°, in order to obtain 196 calculation points. The empirical formula used is Mc. Guire, Si and Midorikawa, Fukushima-Tanaka, and Donovan which were validated with peak ground acceleration data from accelerographs so as to produce an appropriate empirical formula used to calculate the peak ground acceleration value in Padang City. From the validation process it was found that the Fukushima-Tanaka formula is the appropriate formula used to calculate the peak ground acceleration value in the city of Padang with the lowest average error percentage. The results of the calculation show that the highest peak ground acceleration value is in Bungus Teluk Kabung District, which is 69-73 gal, while the lowest peak ground acceleration value is in Koto Tangah District, which is 60-65,5 gal. Based on the peak ground acceleration value, it is known that the intensity of the earthquake in Padang City has a scale of VI MMI.